The presence of animals in hospital facilities: A preliminary study on the opinion of doctors, healthcare workers, and students in Sardinia - Sanna Passino, Eraldo; Sechi, Sara; Mollica, Alessandra; Demaria, Fabrizio; Cocco, Raffaella (SAGE open medicine, 2024)
Introduction: Contact with pets within healthcare settings is considered worldwide an added value to assistance both in the case of animal-assisted interventions and also when pets are visiting hospitalized owners, due to the special emotional relationship between them and their pets. The goal of this work was to analyze local experiences on access of pets to healthcare facilities using a survey sent to doctors, veterinarians, and students in the region of Sardinia (Italy). Methods: The online survey consisted of 17 questions, with the objective to evaluate knowledge and interest of study participants on some aspects of human–animal interaction with particular reference to potential access of pets to hospitals facilities and nursing homes and to promote an initial social judgment in the medical and healthcare environment. A total of 2484 subjects were invited to participate to the survey through an email explaining the purpose of the study. Statistical analysis on the survey results was conducted by comparing the characteristics of respondents with their answers to animal-assisted-intervention-related questions. Results: Results showed that over 70% of the participants owned an animal; almost 80% of responses showed that survey participants were in favor of animal presence in hospitals; furthermore, the responses showed how the concept of One Health seems not only scarcely established, but also barely known. The large majority of respondents (over 80%) positively responded on questions around the role of animals as co-therapists. Conclusions: On the one hand, this study showed lack of knowledge on the concept of One Health, whose essence is too often unknown and, on the other hand, it confirmed that women may be more inclined to show empathy and sensitivity toward animals. Regarding the profession, students seem more concerned about the introduction of animals into hospitals than healthcare workers.